Application of braided fibre reinforced composite rods in concrete reinforcement - Fangueiro, Raúl (2006)
This paper describes the work that is being done at the University of Minho concerning the development of braided rods for concrete reinforcement. A preliminary research study has been conducted to understand the mechanical behaviour of braided fabrics. Various samples have been produced varying the type of fiber (glass, polyester and aramid), the type of braided fabric (simple, hybrid and core reinforced) and in the latter case, the number of core reinforcing yarns. The tensile properties of these samples have been evaluated and the results presented. The influence of each factor on the tensile properties of braided fabrics has also been analysed and discussed. In order to produce braided reinforced composite rods to use as a concrete reinforcement, a special technique has been developed using a standard vertical braiding machine. The braided reinforced composite materials have been produced in rib structure to improve adhesion between them and the concrete. Special samples have been prepared and tested to evaluate the adherence between both materials involved. The tensile and bending properties of braided reinforced composite rods have been evaluated and the results obtained presented and discussed.